Early preeclampsia and HELLP syndrome in a 20 week pregnant patient - Fatemeh Keighobadi Khajeh; Gholamreza Fareedalaee; Fatemeh Abbasalizadeh (Journal of Emergency Practice and Trauma, 2017)
The first time Weinstein in 1982 described patients with the syndrome of hemolysis, elevated liver enzymes, and low platelet count (HELLP) in pregnant preeclamptic and eclamptic patients. This syndrome is a severe form of preeclampsia or eclampsia. Usually HELLP syndrome occurs at the third trimester and only 15% occur before the 27th week of pregnancy and rarely before the 20th week of pregnancy. We want to present a 30- year old parity 2, gravidity 1 pregnant patient who was pregnant for 20 weeks with preeclampsia and HELLP syndrome. Two hours before arriving to the emergency unit, she felt chest discomfort and went to the nearest clinic to visit a physician. She was then referred to the hospital because of high blood pressure (BP). When she arrived to the emergency unit, she had right upper quadrant and epigastric pain, headache, vomiting, dyspnea, and high BP (185/100). Finally the diagnosis of HELLP syndrome was made. As maternal and fetus mortality and morbidity of HELLP syndrome is high, immediate recognition and treatment is vital to save the lives of both the mother and the fetus